The Diagnostic paracentesis in peritoneal complications of the severe multiple trauma patient - Perdomo, Roberto; Filgueira, José L (Cirugía del Uruguay, 2020)
A report is made of 8 cases with abdominal visceral lesions in conjuntion with multiple injuries, of which 6 with hemoperitoneum and 2 with peritonitis following injury to hollow viscera. Attention is drawn to diagnostic difficulties in this type of patients, particularly in cases of disaster. Delayed detection of actual conditions is one of primary causes of poor diagnosis. The gratifying results of diagnostic paracentesis are described. The procedure was found harmless, readily available and throroughly safe when positive.